Exploring the possible link between increased screen time and malocclusion in children and adolescents: A scoping review - G Murali; Amit Kumar Tamrakar; Akanksha Juneja; Amina Sultan (SRM Journal of Research in Dental Sciences)
Introduction: As screen time becomes an integral part of daily life for children, concerns are emerging about its broader impacts on health, including its potential role in dental development issues. This scoping review was done to examine the connection between excessive screen time and malocclusion. Methods: To assess the relationship between screen time and malocclusion in children and adolescents, a search of the literature was carried out across various platforms (PubMed, JSTOR, Science Direct, Scopus, and Google Scholar). Since no studies were found pertaining to the research question, a broader search was done, with participants’ to the age of 18 years, conducted during the period 2000–2023, and which assessed the relationship between screen time and overall dental health. Results: No studies were available in the literature which addressed the effect of screen time on malocclusion. Most of the current research highlights the relationship between increased screen time and poor eating habits and dental caries in children. Discussion: After analyzing the studies available, a cause-and-effect relationship model has been proposed by the authors. We suggest that excessive screen time may contribute to malocclusion through mechanisms such as poor posture, reduced jaw movement, increased sugar consumption, and delayed dental development. However, as very limited research is available, more studies in this field are needed. Conclusion: The article offers practical recommendations for parents and caregivers to mitigate these risks, including setting limits on screen time, encouraging good posture, promoting a balanced diet, and ensuring regular dental checkups.